Increased plasma dipeptidyl peptidase-4 activities are associated with high prevalence of diabetic nephropathy in Chinese patients with newly diagnosed type 2 diabetes: A cross-sectional study. (March 2016) - Zheng, Tianpeng; Liu, Yihong; Qin, Shenghua; Liu, Hongbo; Zhang, Xiaoxi; Zhao, Hailu
Objective: To investigate the association between plasma Dipeptidyl peptidase-4 (DPP4) activities and diabetic nephropathy in type 2 diabetes. Research design and methods: A total of 1193 newly diagnosed type 2 diabetic subjects were studied. Plasma DPP4 activity, mannose 6-phosphate receptor, inflammatory markers and oxidative stress parameters were measured in all participants. Diabetic nephropathy was defined as the presence of albuminuria or an estimated glomerular filtration rate < 60 mL/min/1.73 m 2 . Results: Participants in the highest quartile of DPP4 activity had higher HbA1c, homeostatic model assessment of insulin resistance, nitrotyrosine, 8-iso-PGF2a, interleukin-6, high-sensitivity C-reactive protein, mannose 6-phosphate receptor, urinary albumin-to-creatinine ratio and lower estimated glomerular filtration rate compared with participants in the lowest quartile (all p < 0.001). DPP4 activities were associated positively with HbA1c, homeostatic model assessment of insulin resistance, nitrotyrosine, 8-iso-PGF2a, interleukin-6, high-sensitivity C-reactive protein, mannose 6-phosphate receptor, urinary albumin-to-creatinine ratio and negatively with estimated glomerular filtration rate (all p < 0.001). In the highest DPP4 quartile, diabetic nephropathy risk was significantly higher (odds ratio: 3.77; 95% confidence interval: 2.34–6.07) than in the lowest quartile after adjustment for potential confounders. This association remained strong (2.85; 1.74–4.68) after further controlling for HbA1c, homeostatic model assessment of insulin resistance, nitrotyrosine and high-sensitivity C-reactive protein. Conclusion: This study shows that increased DPP4 activities are strongly and independently associated with diabetic nephropathy in type 2 diabetes. The associations between DPP4 and diabetic nephropathy, although strong, do not imply causality. There are however plausible mechanisms which could explain such a link.